Colombian Undergraduates: Critical Readers? A Study on Literacy Skills within the Most Demanded Undergraduates in Colombia’s Labor Market (Papeles, 2017)
The purpose of this study is to shed clues on how the Colombian labor market promotes higher reading-writing skills by the undergraduates that finish their studies every year at Colombian universities. Thus, we turn to the Colombian National University looking to make a contrast between the undergraduate programs with a better performance at the standardized public tests, and those programs whose students experience a bigger welcome by the labor market once they finish their studies. Thereby, we find that, in spite of how crucial are reading-writing skills on an individual’sdevelopment, this is not as evident in the working world.
Keywords: Labor Market; Colombian undergraduates; Literacy; Standardized Public Tests; Wages; Skills; Income; Employability